The relationship between marketing practices, capabilities, orientation and performance of the service sector small medium entreprises in Pakistan - Ghouri Arsalan Mujahid (N/A, 2014)
The relationship between marketing practices, capabilities, orientation and performance of the service sector small medium entreprises in Pakistan by Ghouri Arsalan Mujahid,